Generative creations, code, and data: How intellectual property rights over ownership, use, and image apply to higher education (Comparative & International Education Series, 2024)
With the growth of artificial intelligence (AI) within higher education, intellectual property rights related to the intangible assets identified and created through AI has emerged as a central inquiry. Who owns, may use, and may collect monetary gains associated with inventions, artistic or original works, replication of derivative works, literary expressions, source codes, applications, trade names, and innovative processes that emerged from AI? This multi-part question drives the discussion of this chapter through technology, legal, and corporate scientific translations that are critical for higher education scholars, leaders, and pundits. Using three case studies to dissect the core analyses of intellectual property and unveil the key considerations connected with AI, this chapter considers the macro-level issues pertaining to the economic, political, and social contexts and the micro-level factors centered around the legal parameters, technological advancements, and competing interests.https://press.starscholars.org/press/catalog/book/52